Power of dispensing the parish-priest and another presbyter, or a deacon - KRAJCZYŃSKI, JAN (Prawo Kanoniczne, 2012)
The solutions chosen by the legislator in scope of the power of dispensing the parish-priests, other presbyters or deacons, far from rigorism and exclusiveness, come undoubtedly as ones that serve the purpose of protecting subjective rights of the faithful Christians. The clearly distinguished administrative function of the church authority, precise determination of certain bodies that hold of competence to accomplish their specific functions in scope of dispensing, and the last but not least fairly wide powers exercised by the above mentioned Sacred Ministers, constitute significant parts of canonic administration of justice. The statutory regulation of the above mentioned life sphere of the People of God, that allows for adjusting the legal regulation to the very specific situations, comes as a very humane and rational one; the one which is adequate to changeable and specific circumstances of people and things; this regulation at the same time confirms the real legislator’s pastoral concern for the welfare of the faithful people who may face a situation when fulfilling duties stipulated in law provisions may appear as incommensurably heavy or even harmful ones. Getting to know the rules of universal law in the capacity of dispensing the above mentioned Sacred Ministers gives grounds for considering that the legislator, in the very delicate sphere of church life, follows the principle of favor personae and favor boni, but is not guided by the principle of favor legis. Confirming the crucial function of dispensation itself, from the first years of its application associated with reasonable administration, in special circumstances of the individual case the legislator allows to yield the right of law to the person and their spiritual welfare. At the same time, it needs to be added that any extension of the delegated power of dispensing the parish-priests, other presbyters or deacons in extraordinary cases, adopted in the Code of Canon Law, constitutes a step in the right direction, but is not necessarily the optimal and appropriate solution as far as the present living conditions of the faithful Christians are concerned. One may boldly submit the de lege ferenda application so that in case of 1245 canon provision of the Code of Canon Law the word “parish-priest” may be replaced by the phrase: „each presbyter”, which shall at the same time empower wider range of people who may grant dispensation from the obligation of observing a feast day or a day of penance. Such a solution – necessarily preceded by an appropriate formation of presbyters, and those who would take advantage of permanent authority delegated by the presbyters – would comply much better with the complex conditions of modern life of the contemporary Christians; it would also better reaffirm the legislator’s will in order to help the needs of the faithful who are in a special situation as efficiently and as quickly as possible.